How do contract performance rates affect entrepreneurs’ risk-averse attitudes? Evidence from China - Sun, Zenan; Lu, Shen; Huang, Man; Zhuang, Jincai; Vaca Lucero, Andrea Maria; Osei, Charles Dwumfour (Frontiers in Psychology, 2023)
Entrepreneurs’ attitudes toward risk is one of the most critical factors influencing business growth and economic development. Therefore, addressing the influencing factors and formation mechanisms of entrepreneurs’ risk attitudes has become a crucial research endeavor. In this paper, we examine how contract performance rates affect entrepreneurs’ risk attitudes through the mediating effect of subjective well-being as well as assess the moderating effect of the regional business environment on this relationship. The ordered probit regression technique was employed to analyze the data obtained from 3,660 sampled respondents from the 2019 China Household Finance Survey. All analysis was performed using Stata 15.0. The empirical results show that contract performance rates have a substantial positive indirect effect on entrepreneurs’ degree of risk aversion through improved subjective well-being. The regional business environment plays a negative regulatory role in the relationship between contract performance rates and entrepreneurs’ risk aversion. Furthermore, urban–rural heterogeneity appears to consistently determine the extent of the influence of contract performance rates on entrepreneurs’ risk attitudes. Our study contributes to the empirical understanding of entrepreneurs’ investment decisions in the context of urban and rural environments.